KOORDINASI ANTAR ORGANISASI PERANGKAT DAERAH (OPD) DALAM MEMBANTU PENANGGULANGAN ABRASI DI KABUPATEN KEPULAUAN MERANTI TAHUN 2018 - Yunita, Rahma; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Kepulauan Meranti Regency is one of  the five priority areas oftheSingapore/Malaysia/Vietnam RI sea border foundin Riau Province,in addition to the city of Dumai,Bengkalis Regency,Rokan Hilir Regency and Indragiri Hilir.Kepulauan Meranti Regency is one districts in Riau Province which has damage from year to year,especially those dealing directly with the Malacca Strait which has strong sea weaves.This Study aims to find out how the coordination between regional apparatus Organizations in Assisting the Prevention of Abrasion in the Meranti Island Regency,the also to find out the inhibiting factors that have not been optimal in the Kepulauan Meranti regency in 2018.The location of the study was conducted in Selat Panjang,first at the office Regional Development Planning Agency,Regional Secretaiat Office,Office of PUPR Office,Office of regional Disaster Management Agency,Office of Fisheries Office and Coastal Sub-District Heald Office.Furthermore,data collection techniques were carried out by interview,documentation and literature study.The result of this study arethe coordination between the regional apparatus Organizations in the prevention of abrasion in the Meranti Island Regency which  was carried out as an effort to overcome the abrasion in the Meranti Island disctric  has not been running optimally.This is caused by several factors such as lack of facilities and infrastructure,budget and limited authority. * Keywords :Abrasion Mitigation,Coordination,Authority,Bureaucratic.